The progressive android based road rules defensive driver’s license application - Rusere, Tafadzwa (Midlands State University, 2018)
The progressive Road Rules Defensive Driver’s License Application will permit users to practice questions remotely using their devices. The system will give users more satisfaction and comfortability than the current system. The android based application can be accessed from any internet browser across the globe on any active internet garget. This system is used as a practice platform fort defensive driving and will create customer loyalty and build trust in between the company and its clients. A careful analysis of the system was conducted and considerations of what the users expects from the system were noted and considered. Observations, interviews and questionnaires where used as data gathering methodologies to help in development of the system.